The relationship between trait awe and procrastination: A mediated model with moderation - Song, Jinze; Zhang, Chao; Li, Tong (Frontiers in Psychology, 2022)
The current study aims to examine the effect of trait awe on college students’ procrastination with a focus on confirming the mediating role of stress and the moderating role of future time perspective (FTP). Measures of procrastination, trait awe, stress, and future time perspective were completed by 512 Chinese college students. The results indicate that trait awe had a negative effect on procrastination, that stress was a significant mediator between trait awe and procrastination, and that FTP moderated the mediation effect. These findings not only demonstrate the crucial role of awe in alleviating procrastination but also elucidate the underlying mechanisms and relevant populations. Limitations and directions for future research were also discussed.